(untitled) (Development Service Industry Management, 2024)
The article examines the peculiarities of learning management systems. The components of training management systems are considered, including: management of the material and technical base; HR; financial management; educational plans; schedule; attendance; management of the examination of the success of studies; reporting, etc.Проаналізовано існуючі системи для навчання водіїв автотранспортних засобів, таких як: • Еlectronic driving schools and online training; where you can take the entire driver training course online, including theoretical and practical stages; • Driving simulators that allow drivers to practice real safety situations on the streets and roads; • Mobile applications that provide a wide range of functionality, including testing, progress tracking, and more; • Driving behavior monitoring systems. which analyze driving style and provide advice on how to improve it; • Testing and evaluation systems to determine the level of knowledge acquisition and readiness of drivers to obtain a license. The characteristics of driver training management systems, such as LMSb, CATS (Care About the Students), eLearning Server 3000 v2.0 and others, were considered, which made it possible to establish the specifics of their implementation and use. The experience of implementing management systems for the training of motor vehicle drivers in Ukraine and developed countries of the world is analyzed. It was found that developed countries have a more comprehensive set of tools for training drivers. At the same time, Ukraine also has experience in introducing the latest technologies and systems aimed at improving the knowledge of drivers, increasing the level of road safety, and ensuring effective training and navigation. As a result of the conducted research, it was established that modern education management systems are an important tool for improving the quality of education, ensuring flexibility and promoting interaction between participants in the educational process. The implementation of such systems is a necessary component of professional training and certification, which will ensure the correctness and safety of the traffic situation.